HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN KESIAPSIAGAAN PETUGAS KESEHATAN DALAM MENGHADAPI BENCANA GEMPA BUMI DI PUSKESMAS SUKAMERINDU KOTA BENGKULU - Listiana, Devi; Colin, Vellyza (Jurnal Kesehatan Saintika Meditory, 2024)
Earthquake disasters not only cause casualties but can also cause problems in the health sector , therefore strategic steps to minimize the impact, one of which was by preparing the preparedness of health workers, including knowledge and attitudes health worker Puskesmas. This study aims to find out the relationship between knowledge and attitudes with the preparedness of health workers in facing the earthquake disaster in Sukamerindu Health Center in Bengkulu city. This study used an analytical survey design with a correlation approach. The population in this study was all health workers in the Sukamerindu Health Center in Bengkulu, totaling 45 people. The sampling technique of this study is total sampling. This study used primary data obtained from respondents using questionnaires on health workers at the Sukamerindu health center in Bengkulu city. Data analysis was conducted univariately and bivariately . (1) The results of the study were obtained: There was a relationship between knowledge and the preparedness of health workers in dealing with earthquake disasters at the Sukamerindu Health in Bengkulu City. (2) There is a relationship between the attitude and preparedness of health workers in facing the earthquake disaster at the Sukamerindu Health Center in Bengkulu City. The results of the Pearson Chi-Square test were obtained at 40,037 with a continuity correction value or (P-Value 0.000<α or 0.000 < 0.05) then Ho rejected Ha accepted the conclusion is that there is a significant relationship between knowledge with the preparedness of health workers in facing the earthquake disaster at the Sukamerindu Health Center in Bengkulu City. The results of the Pearson chi-square test obtained a value = 21,399 and a continuity correction value or (P-Value 0.000<α or 0.000 < 0.05) then Ho was rejected and Ha was accepted the conclusion was that there was a significant relationship between the attitude and preparedness of health workers in facing earthquakes at the Sukamerindu Health Center in Bengkulu City. It was expected that puskesmas health workers can attend seminars and continue education to a higher level in order to increase knowledge and attitudes about natural disaster emergency response preparedness.  Keywords: Knowledge, Attitude, Earthquake Preparedness